Bevölkerungsmaximum und Bevölkerungsoptimum - Scharlau, Kurt (ERDKUNDE, 1955)
The central problem of population geography is to assess the future possibilities of widening the human living space on the earth. As suggested by H. Schmitthenner, it is necessary to distinguish between creation of real living space, i. e. an areal increase of the present productive regions, and virtual living space, i. e. an increase of production capacity and thus the ability to support a larger number of people from the same area. By making this distinction the question arises of what are population maximum and population optimum respectively. So far a distinction between these terms has seldom been made in the literature of population study. The population maximum is an absolute and ultimate quality to be calculated as the total effect of factors causally connected with each other. The population optimum, on the other hand, is a relative quality. The magnitude of the latter depends on which optimum factors are in each case taken into consideration. Optimum factors are such, which on the basis of a subjective judgement, are a priori held to be most favourable. A solution is thus offered to the contradictions apparent in the varying estimates of the future world population as given by different authors. Since their premises have not been the same, the different calculations are not directly comparable. That such forecasts are of a relative kind is made even clearer if it is appreciated that alterations of production methods and changes of diet within the world population will very likely occur in the future as they have done in the past. It follows that no rigid and unalterable relation between production of foodstuffs and the number of people can be postulated and thus no long term numerical forecasts of population development can be made. This statement cuts away the basis on which the central problem of T. R. Malthus’s population theory is founded that the continuous increase of the world population and the simultaneous relative decrease of the food producing area will bring about the inevitable catastrophe of our planet. This, according to the Neo-Malthusians of the present century, is threatening imminently. In this context the demographic studies of F. W. Notestein and W. S. Thompson warrant close attention by the human geographer. They show that numerical population development is not a process continuing in the same direction, but rather a cyclical process which in all stages of civilization tends to bring about optimum population totals, reflecting conditions of equilibrium between the number of people and the decisive factors of the physical and social environment. An important conclusion is the recognition that the creation and satisfaction of new desires of material and spiritual life will eventually be capable of throttling any Malthusian population growth. Although it is not explicitly stated, the Four Point Programme for the economic development of the underdevel- oped regions of the world aims at this goal in the sphere of population policy. However, a rise in the general living standard and an improvement of the sanitary conditions in the underdeveloped areas will at first certainly result in a further increase in their population which will very likely surpass their optimum numbers. Thus the grave question arises which political consequences will result, possibly already during the next decades, from this mobilization of the population potential of the underdeveloped regions of the world which embrace two-thirds of the entire human race.